FENOMENA MENURUNNYA KEBIASAAN BERJALAN KAKI KARENA PERKEMBANGAN TRANSPORTASI MODERN - Najwa Khoirotun Nisa; Mawardi Nurullah (CV. Denasya Smart Publisher, 2026)
The declining habit of walking has become a significant issue in the development of modern cities. Easy access to motorized transportation, shifts in mobility patterns, and the deterioration of public spaces have led people to rely increasingly on private vehicles even for short-distance travel. Recent studies show that environmental factors, safety perceptions, connectivity, and the quality of pedestrian facilities play crucial roles in reducing walking activity. This article examines the phenomenon through a literature review of various studies related to walkability and pedestrian behavior. The findings indicate that modern transportation has shifted the culture of walking, especially in urban areas. Built environments that are unsupportive such as narrow and poorly maintained sidewalks, congested intersections, and limited green spaces further hinder pedestrian activity.